PSYCHOLOGICAL DIAGNOSTICS OF STUDENTS ADAPTATION TO UNIVERSITY STUDIES - Olga A. Molokova (Образование и наука)
Aim. The solution version of one of problems of psychology andpedagogical escort of students at the initial stage of their adaptation to training in higher education institution is stated in the study. Such maintenance obligatory includes diagnostics of a psychological state of pupils that in a traditional state demands considerable expenses by as teachers’ and first-year students’ forces and time. Possibility of elimination of this shortcoming is presented.Methods. The methods involve the modified Sklyayn’s technique which description is presented in K. Rogers’s works; the technique of the personal differential definition; the technique of definition of the psychological satisfaction in various vital spheres. Students’ relation to the research was found out during anonymous poll.Results. It is shown that, despite the positive relation to psychological researches from the majority of respondents, there is a problem of the obvious or latent unwillingness of some first-year students to participate in surveys and test work caused by work content and its duration. The alternative to tiresome measurements of indicators of adaptation of pupils to training in higher education institution is presented – the express diagnostics reduce time of monitoring and allow teachers to get students interested. Comparison of the results received at use of Sklyayn’s technique and a technique «Personal differential» shows that they investigate the same phenomenon at nonverbal and verbal levels: correlation of persons’ «real self» and «ideal self». However, if creation of verbal formulations of the person relation to what he/she is, and to what he/she wants to be, can cause difficulties by the examinee, the nonverbal diagnostics turned to subconsciousness, is not only simpler, but also reflects a psychological state of the person more precisely.Scientific novelty. Modification of the technique by Sklyayn is proposed; it corresponds to bases of the personal aligned approach to psychology and pedagogical maintenance, the opportunity expanding it at the expense of speed and assessment non-complication of an emotional condition of the personality.Practical significance. Timely detection of difficulties which are experienced by students, starting training in higher education institution, helps improve educational process. Efficiency and advantage of application of nonverbal express diagnostics consists in designing conditions for inclusion in research of the student as the subject of this activity, and offers the possibility to discuss the received results with the pupil immediately following the work.